The relevance of Kalaam to comparative religion - Shehu, Fatmir Mehdi (2018)
The main objective of this study is to show the clear relevance of ‘Ilm al-Kalam (Science of Logical Arguments) to the scholarship of comparative religion. Especially in the aspect of dealing with the study of other religions by showing the approach of Muslim Mutakalimun and the Western scholars.